Gambaran Pengetahuan Masyarakat Tentang Penggunaan Telemedicine di Dusun Peron - Nannyk Widyaningrum; Muhlizardy Muhlizardy; Viviana Rahmawati; Retno Tri Utami (Lembaga Pengembangan Kinerja Dosen, 2024)
One form of evolution in telemedicine health services, which is a reaction from society to the increasingly rapid development of science and technology. In this era of globalization and digital, the concept contained in telemedicine embodies the efficiency of medical services so that satisfaction with services will be achieved well. The aim of this research is to determine the description of public knowledge about telemedicine in Peron Hamlet. This research method is a quantitative descriptive method by distributing questionnaires. The research method is a descriptive survey, sampling using a purposive sampling method with a sample size of 70 respondents. The results of the research show that the level of public knowledge regarding telemedicine in Peron Hamlet is categorized as good (5%), quite good (5%), not good (80%), and not good (10%). So from the research results it can be concluded that the description of the level of knowledge about telemedicine in Peron Hamlet is in the poor category.